Analysis of Principled Instruments of âIntellectualsâ Stipulationâ with the Method of âExamining the Components of Its Words and Analysis of Functions and Conjecturesâ - Ã˜Â´Ã›ÂŒÃ˜Â±Ã˜Â§Ã˜Â²Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã˜Â±Ã˜Â¶Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Intellectualsâ stipulation is a principled instrument, that on one hand its sides and components have not been explored into in principles and on the other hand the mechanism of its acquisition to be used in jurisprudence has not been provided. In this article, with an examination of the definitions available about intellectualsâ stipulation and analysis of its application in jurisprudence and principles, this principled instrument will be scrutinized and after uncovering its sides and components and explaining its difference with âintellectualsâ unanimityâ, the mechanisms employed in jurisprudence and principles for acquiring it will be examined and finally the mechanism for relying on intellectualsâ stipulation in jurisprudence and principles will be suggested.